Análise das condições de desaguamento de lodos de ETEs em BAG's: o caso da ETE-Limoeiro - Presidente Prudente-SP - Boina, Welliton Leandro de Oliveira (Universidade Federal de São Carlos, 2012)
Substances in Sewage Sanitary exert deleterious effects on bodies of water; the organic matter which is present may cause a decrease in concentration of dissolved oxygen, killing fish and other aquatic organisms, eutrophication by the presence of nutrients causing an accelerated growth of algae that give odor, taste and biotoxins to the water,darkening and siltation of the watercourse. In this scenario, it is of great importance the need for sewage treatment. However, in the treatment process, occurs the production of sludge rich in organic matter and nutrients, known as sewage sludge. This residue at the end of the treatment process should receive special attention, requiring proper disposal. Moreover, it is found that several sewage treatment projects do not include the final destination of the sludge that is produced, which results in the partial annulment of the benefits of collecting and treating collected wastewater. Therefore, this study presents results of analyzes performed on sludge from sewage treatment contained in BAG's of Geotextile Blanket of ETE-Limoeiro / SABESP, located in the city of Presidente Prudente, SP. The objective of this work was to characterize the physico-chemical and microbiological parameters in accordance with Resolution N° 375/06 of Conselho Nacional do Meio Ambiente CONAMA, and evaluate the efficiency of dewatering of sludge. Based on this, the analysis of identification and quantification of heavy metals showed values below the maximum allowed concentrations in sludge. Regarding the assessment of macro and micronutrients, analysis showed that the sludge has significant amounts of essential nutrients to the soil and plants and it can be used for this purpose after specific treatment. Regarding the biological tests for quantification of fecal coliforms, the obtained concentrations showed values that were established for the sludge Class B. The sludge was also evaluated for stability using the relation between volatile solids and total solids. This relation presented results for SV/ST below 0.70 which allowed defining the sludge as stable according to Resolution 375/06. However, the evaluation of the water removal process showed commitment of the dewatering efficiency according to the characteristics of the sludge generated in the Sewage Treatment Plant. Geotêxtil da ETE-Limoeiro / SABESP, localizada no Município de Presidente Prudente-SP. O objetivo central desta pesquisa foi à caracterização dos parâmetros físico-químicos e microbiológicos em conformidade com a Resolução Nº 375/06 do Conselho Nacional do Meio Ambiente CONAMA, e a avaliação da eficiência do processo de remoção de água dos lodos. Ante o exposto, as análises para identificação e quantificação de metais pesados apresentaram valores abaixo das concentrações máximas permitidas em lodos. Em relação à avaliação de macro e micronutrientes, as análises demonstraram que o lodo possui quantidades significativas de nutrientes essenciais aos solos e plantas, podendo ser utilizado para esta finalidade após tratamento específico. Referente às análises biológicas para quantificação de coliformes termotolerantes, as concentrações obtidas apresentaram valores estabelecidos para lodos Classe B. Os lodos também foram avaliados quanto à estabilidade através da relação entre sólidos voláteis e sólidos totais. Esta relação apresentou resultados para SV/ST inferiores a 0,70 permitindo definir os lodos como estáveis de acordo com a Resolução 375/06. Entretanto, avaliação do processo de remoção de água, demonstrou comprometimento da eficiência do desaguamento em função das características do lodo gerado na Estação de Tratamento de Esgotos.
Keywords: Saneamento; Lodo; Esgoto sanitário; Estação de tratamento de esgoto; BAG; Desaguamento; Sludge; Sewage Sanitary; Sludge of Sewage Treatment Plant; BAG; Dewatering; ENGENHARIAS